2010
DOI: 10.1371/journal.pone.0015000
|View full text |Cite
|
Sign up to set email alerts
|

Toxic but Drank: Gustatory Aversive Compounds Induce Post-ingestional Malaise in Harnessed Honeybees

Abstract: BackgroundDeterrent substances produced by plants are relevant due to their potential toxicity. The fact that most of these substances have an unpalatable taste for humans and other mammals contrasts with the fact that honeybees do not reject them in the range of concentrations in which these compounds are present in flower nectars. Here we asked whether honeybees detect and ingest deterrent substances and whether these substances are really toxic to them.ResultsWe show that pairing aversive substances with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
101
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 81 publications
(105 citation statements)
references
References 72 publications
(100 reference statements)
3
101
1
Order By: Relevance
“…We observed that during conditioning, restrained locusts did not reject the NHTenriched diet, even at very high concentrations. Tethered honeybees (Ayestaran et al, 2010;Wright et al, 2010) and confined crickets (Matsumoto and MIzunami, 2002) exhibit the same lack of rejection behaviour, ingesting considerable amounts of toxic or bitter substances during associative conditioning. Thus, it is possible that restraint disrupts the behavioral sequence that free-moving locusts use to select or reject food , leading to the acceptance of toxic substances even when they are registered by taste receptors.…”
Section: Discussionmentioning
confidence: 99%
“…We observed that during conditioning, restrained locusts did not reject the NHTenriched diet, even at very high concentrations. Tethered honeybees (Ayestaran et al, 2010;Wright et al, 2010) and confined crickets (Matsumoto and MIzunami, 2002) exhibit the same lack of rejection behaviour, ingesting considerable amounts of toxic or bitter substances during associative conditioning. Thus, it is possible that restraint disrupts the behavioral sequence that free-moving locusts use to select or reject food , leading to the acceptance of toxic substances even when they are registered by taste receptors.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of the honeybee, for instance, experiments performed with harnessed bees in the laboratory could not find clear evidence for bitter taste perception until now [33]. Electrophysiological as well as behavioural analyses performed on several gustatory appendages have shown that bees in the laboratory are quite insensitive to bitter substances [34] and even consume important quantities of them despite their high concentration, toxicity and resulting mortality [35]. However, when tested in free-flight conditions, bees exhibit avoidance of highly concentrated bitter substances thus suggesting that gustatory thresholds may dramatically vary with the experimental situation and the possibility of expressing avoidance in an overt way [36].…”
Section: Peripheral Taste Encoding (A) the Case Of Insectsmentioning
confidence: 99%
“…This assay of food consumption described by Tiedeken et al 7 revealed that bees can detect bitter compounds in solutions. However, this assay was unable to distinguish taste from post-ingestive processes such as malaise that could also affect feeding behavior over this time interval [8][9][10] .…”
Section: Introductionmentioning
confidence: 95%